2015
DOI: 10.1136/bmjopen-2015-009246
|View full text |Cite
|
Sign up to set email alerts
|

Supervised pharmacy student-led medication review in primary care for patients with type 2 diabetes: a randomised controlled pilot study

Abstract: ObjectiveTo pilot and feasibility-test supervised final year undergraduate pharmacy student-led medication reviews for patients with diabetes to enable definitive trial design.MethodThird year pharmacy students were recruited from one UK School of Pharmacy and trained to review patient's medical records and provide face-to-face consultations under supervision while situated within the patient's medical practice. Patients with type 2 diabetes were recruited by postal invitation letter from their medical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 33 publications
0
34
0
17
Order By: Relevance
“…(Katch & Mead, 2010) It may also be useful for University education to include training in this topic. (Adams et al, 2015;Chen, Plake, Yehle, & Kiersma, 2011;Westberg, Bumgardner, Brown, & Frueh, 2010) The results of this study also suggested that, when professional services are provided, they modify patients' 'Self-efficacy' that in turn improves 'PPI' vs. usual care. Therefore, those services focused on patient education would be the most influential on 'PPI' .…”
Section: Discussionmentioning
confidence: 60%
“…(Katch & Mead, 2010) It may also be useful for University education to include training in this topic. (Adams et al, 2015;Chen, Plake, Yehle, & Kiersma, 2011;Westberg, Bumgardner, Brown, & Frueh, 2010) The results of this study also suggested that, when professional services are provided, they modify patients' 'Self-efficacy' that in turn improves 'PPI' vs. usual care. Therefore, those services focused on patient education would be the most influential on 'PPI' .…”
Section: Discussionmentioning
confidence: 60%
“…When pairs of pharmacy students provided level two and three medication reviews to 67 patients with diabetes the intervention group had a lower post-intervention HbA1c (56.32 ± 11.5%) than the control group (59.68 ± 13.2%, n = 66, p = 0.14) who received usual care [31]. Each student pair attended to four patients [31]. Within intervention group change was − 0.49% compared to − 0.03% in the control group [31].…”
Section: Hba1cmentioning
confidence: 95%
“…Student-led health interventions were primarily located in a clinic setting [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Of the student-led clinics, five studies described the service provided as a "free clinic" [33,36,41,42,44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations